Efecto de la sustitución del zinc bacitracina por un complejo nutricional natural (mezcla de prebióticos, probióticos, ácidos orgánicos y enzimas) sobre la performance de patos muscovy (cairina moschata) - Capcha Rojas, Elizabeth (2013)
The present study aims to evaluate the performance of muscovy ducks (Cairina moschata) bacitracin zinc substituting for natural nutritional complex (mixture of prebiotics, probiotics, organic acids and enzymes) as natural growth promoter. 500 were used for this race muscovy ducks, 250 birds per treatment of both sexes, distributed completely at random, the farm is located in the district of Huanchaco, Trujillo Province, Department of La Libertad, at an altitude of 50msnm. The treatments were: T0: 500 ppm of zinc bacitracin and T1: 3500 ppm of natural nutritional complex. We evaluated weight gain, feed intake, feed conversion, morbidity rate, mortality rate, carcass yield and cost benefit ratio. Each treatment was fed balanced rations according to the nursery stage, which had isoenergetic and isoprotéicos levels. Final weights and increased total weight achieved were not significantly different between treatments (P> 0.05), 3702.8 g to 3739 g for T0 and T1, and of 2,910 g to 2,919 g for T0 and T1 respectively. The largest total food consumption was won with 11 107,2 g T0 treatment followed by T1 10 689,9 g with significant differences between treatments (P <0,05). The best feed conversion was shown by 3.79 T1 with existing significant difference (P <0,05). Likewise, no significant differences between treatments (P> 0.05) for the rate of morbidity and mortality, but there was numerical difference, obtained for T1: T0 1.6% and 2%, and for T0: 0.8% and T1: 0.4% respectively. For carcass yield statistically significant differences were found (P <0.05) in favor of treatment supplemented with natural nutritional complex compared to the control, in males the highest yield obtained at T1 with 83.02% and females at T1 obtained with 82.79%. We conclude that the natural nutritional complex can replace APC because they are obtained similar performance.